The catalytic inhibitor epacadostat can affect the non-enzymatic function of IDO1 - Panfili, Eleonora; Mondanelli, Giada; Orabona, Ciriana; Gargaro, Marco; Volpi, Claudia; Belladonna, Maria Laura; Rossini, Sofia; Suvieri, Chiara; Pallotta, Maria Teresa (Frontiers in Immunology, 2023)
Indoleamine 2,3-dioxygenase 1 (IDO1) is a tryptophan metabolizing enzyme chronically activated in many cancer patients and its expression and activity correlate with a poor prognosis. In fact, it acts as an immune regulator and contributes to tumor-induced immunosuppression by determining tryptophan deprivation and producing immunosuppressive metabolites named kynurenines. These findings made IDO1 an attractive target for cancer immunotherapy and small-molecule inhibitors, such as epacadostat, have been developed to block its enzymatic activity. Although epacadostat was effective in preclinical models and in early phase trials, it gave negative results in a metastatic melanoma randomized phase III study to test the benefit of adding epacadostat to the reference pembrolizumab therapy. However, the reason for the epacadostat failure in this clinical trial has never been understood. Our data suggest that a possible explanation epacadostat ineffectiveness may rely on the ability of this drug to enhance the other IDO1 immunoregulatory mechanism, involving intracellular signaling function. These findings open up a new perspective for IDO1 inhibitors developed as new anticancer drugs, which should be carefully evaluated for their ability to block not only the catalytic but also the signaling activity of IDO1.